Production of activated carbon from malt bagasse with chemical activation using different activating agents (Research, Society and Development, 2022)
Brazil is the third largest beer producer in the world, reaching approximately 14 billion liters per year. If, on the one hand, the expansion of the brewing sector in the country produces a significant increase in the Brazilian GDP, it also causes environmental impacts inherent to the process, since different residues are produced during production and the main one is malt bagasse. This work aimed to investigate the use of malt bagasse through the production of coal via hydrothermal synthesis with subsequent chemical activation by pyrolysis. First, the parameters time (4, 14 and 24h) and temperature (150, 175, 225 and 250 ºC) of hydrothermal carbonization were evaluated, having as a response the efficiency of removal of methylene blue dye in aqueous solution. Subsequently, three activating agents (KOH, H3PO4 and ZnCl2) were used in two mass proportions (1:1 and 2:1) for the production of activated carbons. The different conditions were evaluated in terms of surface area (SBET) and adsorption efficiency. Chemical activation was able to increase the surface area of the carbons by approximately 200 times. Activated carbon with KOH showed better performance in removing the dye, reaching an efficiency of 95.39% under the conditions submitted. The increase in the proportion of activating agent led to greater adsorption efficiencies, as it increased the surface area of activated carbons. All coals showed a predominance of mesopores, confirmed by N2 adsorption and desorption isotherms and pore size distribution.